2018
DOI: 10.1111/ajad.12731
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of alcohol consumption in U.S. military veterans: Results from the National Health and Resilience in Veterans Study

Abstract: Four predominant trajectories of alcohol consumption were identified. Targeting MDD and related interpersonal factors such as attachment style and social support in population-based prevention and treatment initiatives may help prevent, mitigate, and promote recovery from excessive alcohol consumption in veterans. (Am J Addict 2018;XX:1-8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Nearly 1 in 5 soldiers reports problems with social support (Griffith, 2017), and poor postdeployment social support has been associated with a greater odds of PTSD (Bloeser et al, 2014), depression (Bloeser et al, 2014), anger (Vest et al, 2017), violence (Van Voorhees et al, 2018, and excessive drinking (Fuehrlein et al, 2018). Previous research by Romero et al demonstrated that family social support buffered the effects of avoidant coping strategies on post-deployment mental health (Romero et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 1 in 5 soldiers reports problems with social support (Griffith, 2017), and poor postdeployment social support has been associated with a greater odds of PTSD (Bloeser et al, 2014), depression (Bloeser et al, 2014), anger (Vest et al, 2017), violence (Van Voorhees et al, 2018, and excessive drinking (Fuehrlein et al, 2018). Previous research by Romero et al demonstrated that family social support buffered the effects of avoidant coping strategies on post-deployment mental health (Romero et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although reasonable, this is admittedly an unusual finding. Some researchers have found links between depressive disorder and more excessive drinking trajectories as opposed to recovering drinkers [ 3 ], while others have found no systematic link between episodes of emotional dysregulation and episodes of alcohol problem use, as to whether the emotional regulation issues preceded, co-occurred, or followed the alcohol use [ 66 ] and no link between having (or not having) depression and anxiety disorders and remission from alcohol dependence [ 15 ]. The inconsistencies here deserve further study and investigation with respect to potential moderators or interaction effects in the internalizing—alcohol use relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the DoD's prospective Millennium Cohort Study of service members and Veterans ( Ryan et al, 2007 ) previously documented that combat deployment and being Reserve/National Guard were risk factors for both initiation and relapse of unhealthy alcohol use, and that separation from military service was a risk factor for relapse ( Jacobson et al, 2008 ; Williams et al, 2015 ). Other studies have shown a high proportion of unhealthy alcohol use among Reserve/Guard personnel ( Milliken et al, 2007 ; Allison-Aipa et al, 2010 ) and Veterans ( Calhoun et al, 2015 ; Fuehrlein et al, 2018 ). Further, population-based surveys administered to Active Duty military personnel showed increased rates of heavy and binge drinking over a 10-year period, with higher rates among combat-exposed personnel compared with noncombat-exposed personnel ( Bray et al, 2013 ), indicating that active duty combat deployers may be at risk for chronic drinking.…”
mentioning
confidence: 93%
“…Heavy episodic drinking—a particularly risky pattern of unhealthy alcohol use that elevates risk for alcohol use disorder ( Saha et al, 2007 )—is especially common among younger service members ( Jacobson et al, 2008 ; Bray et al, 2013 ). Further, alcohol use disorder with concurrent mental disorders is prevalent among US Veterans ( Fuehrlein et al, 2018 ). Although factors associated with unhealthy alcohol use among service members and Veterans have been well-described in cross-sectional analyses ( Burnett-Zeigler et al, 2011 ), few studies have investigated the factors associated with continued, or chronic, unhealthy alcohol use over time.…”
mentioning
confidence: 99%